2022
DOI: 10.3390/agronomy12092082
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Plant-Growth-Promoting Rhizobacteria Improves Strawberry Growth and Flowering with Soil Salinization and Increased Atmospheric CO2 Levels and Temperature Conditions

Abstract: Biofertilization with plant-growth-promoting rhizobacteria (PGPR) can positively affect the growth and health of host plants and reinforce their tolerance of stressors. Here, we investigate the use of isolated PGPR consortia from halophytes to improve strawberry growth and flowering performance under saline and elevated CO2 and temperature conditions. Growth, flower bud production, and the photosynthetic apparatus response were determined in strawberry plants grown at 0 and 85 mmol L−1 NaCl and in two atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…These microbial associations have been shown to increase plant size and biomass, thereby influencing pollinator behaviour and ultimately impacting plant yield (Backer et al, 2018). In line with these findings, numerous studies have consistently demonstrated that inoculating soil with PGPR leads to increased flower production in various ornamental and crop plants (Göre & Altin, 2006;Kumar et al, 2016;Kumari et al, 2016;Lyu et al, 2022;Nordstedt et al, 2020;Redondo-Gómez et al, 2022). Our results support this trend, as the inoculation of B. amyloliquefaciens on both cultivated and wild tomato species resulted in increased flower production and biomass.…”
Section: Olfactometry Bioassayssupporting
confidence: 87%
“…These microbial associations have been shown to increase plant size and biomass, thereby influencing pollinator behaviour and ultimately impacting plant yield (Backer et al, 2018). In line with these findings, numerous studies have consistently demonstrated that inoculating soil with PGPR leads to increased flower production in various ornamental and crop plants (Göre & Altin, 2006;Kumar et al, 2016;Kumari et al, 2016;Lyu et al, 2022;Nordstedt et al, 2020;Redondo-Gómez et al, 2022). Our results support this trend, as the inoculation of B. amyloliquefaciens on both cultivated and wild tomato species resulted in increased flower production and biomass.…”
Section: Olfactometry Bioassayssupporting
confidence: 87%
“…Early flowering might be due to the indirect effect of PGPR, which can increase the availability of nutrients in the soil and enhance different physiological processes. Redondo-Gómez et al (2022) reported flower bud induction in strawberry plants after inoculation with PGPRs and colonization by Paenibacillus lentimorbus also resulted in more flowers and seeds in tobacco, as reported by Kumar et al (2016). It may be hypothesized that early flowering in healthy plants of A. paniculata may reduce its life cycle.…”
Section: Discussionmentioning
confidence: 66%
“…In summary, Vitis vinifera, when inoculated with the PGPR consortia, had a significant amelioration effect on heatwave-induced stress. These consortia were designed with tested and proven plant growth-promoting rhizobacteria that presented great bioinoculant potential during in vitro assays [27,28] and were built with no differentiating factor among them; however, superior oxidative protection and overall fitness were seen in consortium 2. Consortia effectiveness variation can have many explanations, including biotic and abiotic stress sensitivity [92], soil biochemistry [93] and leaf surface biochemistry [94].…”
Section: Discussionmentioning
confidence: 99%
“…Salt marshes are unique ecosystems that are exposed to high salinity and fluctuations in water levels, making them a potential source of PGPR with stress tolerance properties [24]. The bioaugmentation of plants with these marine PGPR has been shown to aid the plants in resisting and overcoming several abiotic challenges from nutrient deprivation [25] and osmotic stress [26,27], including thermal and extreme stress [28,29]. Moreover, a single strain microorganism usage does not allow the activation of all possible growth-promoting mechanisms; thus, in order to elicit all potential traits, the application of PGPR consortia is increasingly more common in agricultural practices and is of current interest in research [28,30].…”
Section: Introductionmentioning
confidence: 99%